Stroke Among Young West Africans Evidence From the SIREN (Stroke Investigative Research and Educational Network) Large Multisite Case–Control Study. (2019)
Background and purpose: Stroke in lower and middle-income countries affects a young and productive age group. Data on factors associated with stroke in the young are sorely lacking from lower and middle-income countries. Our objective is to characterize the nature of stroke and its risk factors among young West Africans aged <50 years old. Methods: The SIREN (Stroke Investigative Research and Educational Network) is a multicenter, case-control study involving 15 sites in Nigeria and Ghana. Cases included adults aged ≥18 years with computed tomography/magnetic resonance imaging-confirmed stroke. Controls were age-and gender-matched stroke-free adults recruited from the communities in catchment areas of cases. Comprehensive evaluation for vascular, lifestyle, and psychosocial factors was performed. We used conditional logistic regression to estimate odds ratios and population attributable risks with 95% confidence intervals. Results: Five hundred fifteen (24.3%) out of 2118 cases enrolled were <50 years old. Among subjects <50 years old, hemorrhagic stroke proportion was 270 (52.5%) versus 245 (47.5%) for ischemic strokes. Etiologic subtypes of ischemic strokes included large artery atherosclerosis (40.0%), small vessel disease (28.6%), cardioembolism (11.0%), and undetermined (20.4%). Hypertension (91.7%), structural lesions (3.4%), and others (4.9%) were causally associated with hemorrhagic stroke. Six topmost modifiable factors associated with stroke in descending order of population attributable risk (95% confidence interval) were hypertension: 88.7% (82.5%-94.8%), dyslipidemia: 48.2% (30.6%-65.9%), diabetes mellitus: 22.6% (18.7%-26.5%), low green vegetable consumption: 18.2% (-6.8%-43.2%), stress: 14.5% (4.9%-24.1%), and cardiac disease: 8.4% (5.8%-11.1%). Conclusions: The high and rising burden of stroke among young Africans should be curtailed via aggressive, population-wide vascular risk factor control.